MANAJEMEN PRODUK KEMBALIAN DI ERA PERSAINGAN GLOBAL: OPTIMALISASI PROSES RECALL, RETUR, DAN SELF-INSPECTION DALAM RANTAI PASOK MODERN - Annur Tasya Alfiati; Riska Hidayah; Nor Latifah (PT. Hasba Edukasi Mandiri, 2025)
Product return management, including recall, return, and self-inspection processes, is a crucial aspect in maintaining product quality and consumer satisfaction in global supply chains. Globalization has introduced new challenges in managing more complex product returns, requiring more advanced strategies and technologies to ensure efficiency and effectiveness in these processes. Technologies such as AI, machine learning, and blockchain provide solutions for optimizing recall, return, and self-inspection management by accelerating issue detection and improving transparency. Collaboration between suppliers, producers, and distributors also plays a significant role in identifying problems early. This article provides an overview of the importance of effective product return management and how technology and collaboration can assist companies in addressing challenges in global supply chains.